2015
DOI: 10.34040/ijcb.5.1.2015.68
|View full text |Cite
|
Sign up to set email alerts
|

Insilico Drug Prediction and Validation of Lead Candidates on Plasmodium Falciparum Erythrocyte Membrane Protein 1(pfemp1) Against Malaria

Abstract: Malaria is an infectious disease caused by protozoan of the genus Plasmodium. It is transmitted by bite from infected female Anopheles mosquito. Plasmodium falciparum erythrocyte membrane protein 1 (PfEmp1), an antigen that is responsible for the immune evasion of the protozoan. This protein has adhesive properties that cause the infected erythrocytes to bind to the endothelial lining of the blood vessel, thus preventing the infected cells from getting filtered by the spleen. It is found that there is an inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Furthermore, it has been suggested that PPI inhibition by peptides, peptidomimetics, or small-molecule inhibitors may have the potential to interfere with binding domains for malarial targets [14]. The PPIs involved in host pathogen interactions are considered important targets for novel anti-malarial interventions [17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been suggested that PPI inhibition by peptides, peptidomimetics, or small-molecule inhibitors may have the potential to interfere with binding domains for malarial targets [14]. The PPIs involved in host pathogen interactions are considered important targets for novel anti-malarial interventions [17].…”
Section: Introductionmentioning
confidence: 99%